ANALISIS WACANA KRITIS TERHADAP REPRESENTASI KEKUASAAN DALAM BERITA POLITIK TENTANG PEMILU - Malikha, Usrin (Jurnal Tinta, 2023)
This study aims to reveal the representation of power and ideology in online political news texts related to the 2024 General Election in Indonesia. Using a descriptive qualitative approach and the Critical Discourse Analysis (CDA) model proposed by Norman Fairclough, this research analyzes news articles from several widely accessed national online media outlets. The main focus of the study lies in identifying linguistic strategies employed by the media to construct political narratives and ideological tendencies within the texts. The findings show that the media utilize various discursive strategies, such as framing, word choice, and specific syntactic structures, to shape positive or negative representations of political figures and parties. These results indicate that news texts are not neutral but function as instruments for reproducing power and ideology that influence public perception. This research is expected to contribute to the development of critical media literacy among readers and enrich the field of critical linguistics, particularly in the context of education and political communication.